Negative electrode active material, electrochemical device, and electronic apparatus
By using amorphous carbon with a specific pore volume distribution as the negative electrode active substance in a sodium ion battery, the problem of being unable to meet the high energy density and high cycle life at the same time in the prior art is solved, and the energy density and cycle performance of the battery are improved.
Patent Information
- Application Number
- CN202311414247.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
Existing sodium ion batteries cannot meet the needs of high energy density and high cycle life at the same time.
Amorphous carbon with a specific pore volume distribution is used as the negative electrode active material, and the coordination and synergy of ions, electrolyte molecules and conductive agents are optimized by adjusting the distribution ratio of amorphous carbon in different pore size intervals.
The energy density and cycling performance of the battery are improved, and excellent dynamic performance, energy density and cycling performance are achieved.
Smart Images

Figure BDA0004519285810000091 
Figure BDA0004519285810000101 
Figure BDA0004519285810000111
Abstract
Description
Technical Field
[0001] The invention relates to a negative electrode active material, an electrochemical device and an electronic device. Background Art
[0002] 2023 is known as the first year of commercialization of sodium-ion batteries. Sodium-ion batteries have become a potential alternative to lithium-ion batteries or lead-acid batteries in some areas due to their rich raw material resources and low cost. Compared with lithium-ion batteries, sodium-ion batteries currently mainly use active materials such as soft carbon and hard carbon as negative electrode materials, but their gram capacity is 200-320mAh / g and their compaction density is 0.9-1.0g / cc, which is significantly lower than the gram capacity and compaction density of graphite, the negative electrode material of lithium-ion batteries. Although some modification methods can increase the gram capacity of hard carbon to 350mAh / g or even higher, its compaction density also decreases accordingly, accompanied by problems such as processing difficulties and reduced cycle life.
[0003] At present, the improvement of negative electrode active materials for batteries mainly lies in the selection of the types of components in the negative electrode active materials, the relationship between the amounts of each component, and the sphericity and regularity of certain component particles. However, after the above improvements to the negative electrode active materials, the effect of simultaneously improving the energy density and cycle life of the battery, especially the sodium ion battery, is not ideal. Therefore, it is urgent to develop a negative electrode active material that can take into account both energy density and cycle life. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defect that the battery in the prior art cannot simultaneously meet the requirements of high energy density and high cycle life, and to provide a negative electrode active material, an electrochemical device and an electronic device. The electrochemical device prepared by using the negative electrode active material can simultaneously have excellent kinetic performance, energy density and cycle performance.
[0005] In a first aspect, the present invention provides a negative electrode active material, wherein the negative electrode active material comprises amorphous carbon, and the amorphous carbon satisfies the following conditions:
[0006] 10%≤A≤30%, wherein A is the percentage of the total volume of pores with an inner diameter of less than 2 nm in the amorphous carbon to the total volume of pores with a diameter of less than 100 nm;
[0007] 10%≤B≤30%, wherein B is the percentage of the total volume of pores with an inner diameter of 2-10 nm in the amorphous carbon to the total volume of pores with a diameter less than 100 nm;
[0008] 50%≤C≤70%, wherein C is the percentage of the total volume of pores with an inner diameter of 10-100 nm in the amorphous carbon to the total volume of pores with a diameter less than 100 nm;
[0009] A+B+C=100%;
[0010] The amorphous carbon includes hard carbon.
[0011] In a second aspect, the present invention provides an electrochemical device, comprising a negative electrode sheet, the negative electrode sheet comprising a current collector and a negative electrode material layer located on the current collector, the negative electrode material layer comprising the negative electrode active material and the conductive agent as described above, the amorphous carbon and the conductive agent satisfy the following conditions:
[0012] 1≤D1 / D2≤10, wherein D1 is the average pore size of pores with a diameter of 10-100 nm in the amorphous carbon, and D2 is the particle size of the conductive agent.
[0013] In a third aspect, the present invention provides an electronic device comprising the electrochemical device as described above.
[0014] The positive and progressive effects of the present invention are:
[0015] The present invention provides an amorphous carbon with a specific pore volume distribution. By adjusting the distribution ratio of amorphous carbon with different pore diameters in the negative electrode active material, specifically the proportion of amorphous carbon with pore diameters in different diameter ranges in the amorphous carbon with a pore diameter of less than 100 nm, ions, electrolyte molecules and conductive agents can cooperate synergistically in a suitable ratio, thereby improving the energy density and cycle performance of the battery. DETAILED DESCRIPTION
[0016] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0017] Negative active material
[0018] In the negative electrode active material described in the first aspect of the present invention, the negative electrode active material includes amorphous carbon, and the amorphous carbon satisfies the following conditions:
[0019] 10%≤A≤30%, wherein A is the percentage of the total volume of pores with an inner diameter of less than 2 nm in the amorphous carbon to the total volume of pores with a diameter of less than 100 nm;
[0020] 10%≤B≤30%, wherein B is the percentage of the total volume of pores with an inner diameter of 2-10 nm in the amorphous carbon to the total volume of pores with a diameter less than 100 nm;
[0021] 50%≤C≤70%, wherein C is the percentage of the total volume of pores with an inner diameter of 10-100 nm in the amorphous carbon to the total volume of pores with a diameter less than 100 nm;
[0022] A+B+C=100%;
[0023] The amorphous carbon includes hard carbon.
[0024] Those skilled in the art generally understand that amorphous carbon includes hard carbon and soft carbon. In the embodiment of the present invention, the weight percentage of hard carbon in amorphous carbon is more than 90%.
[0025] The inventors believe that the volume ratio of pores with an inner diameter of less than 2nm in amorphous carbon directly contributes to the capacity of amorphous carbon to store sodium ions, and sodium exists in the form of metal clusters in pores less than 2nm. When the A ratio increases, it helps to increase the capacity of amorphous carbon, thereby improving the energy density; when the A ratio is too large, the pore structure will lead to a decrease in the compaction density, resulting in a decrease in the energy density of the battery;
[0026] The volume ratio of pores with an inner diameter of 2-10 nm in amorphous carbon affects the entry of electrolyte molecules, thereby affecting the liquid absorption and retention capacity of amorphous carbon and improving ion transport. When the B ratio increases, it helps to improve the dynamics and cycle performance of the battery; when the B ratio is too large, it will affect the ability of amorphous carbon to store ions in micropores, resulting in a decrease in the capacity of amorphous carbon, thereby causing a decrease in the energy density of the battery;
[0027] The volume ratio of pores with an inner diameter of 10-100nm in amorphous carbon affects the entry of conductive agents. The electronic conductivity of amorphous carbon is generally worse than that of conductive agents. When conductive agents enter pores with an inner diameter of 10-100nm in amorphous carbon, the electronic transmission of amorphous carbon can be significantly improved. When the C ratio increases, it helps to improve the kinetics and cycle performance of the battery; when the C ratio is too large, it will affect the ability of amorphous carbon to store ions in micropores, resulting in a decrease in the capacity of amorphous carbon, thereby causing a decrease in the energy density of the battery.
[0028] In some optional embodiments, the amorphous carbon satisfies: 17%≤A≤27%.
[0029] In some optional embodiments, the amorphous carbon satisfies: 16%≤B≤24%.
[0030] In some optional embodiments, the amorphous carbon satisfies: 59%≤C≤66%.
[0031] In a specific embodiment, the amorphous carbon satisfies: A=17.2%, B=23.5%, C=59.3%.
[0032] In a specific embodiment, the amorphous carbon satisfies: A=10%, B=23.5%, C=66.5%.
[0033] In a specific embodiment, the amorphous carbon satisfies: A=30%, B=23.5%, C=46.5%.
[0034] In a specific embodiment, the amorphous carbon satisfies: A=17.2%, B=10%, C=72.8%.
[0035] In a specific embodiment, the amorphous carbon satisfies: A=17.2%, B=30%, C=52.8%.
[0036] In a specific embodiment, the amorphous carbon satisfies: A=17.2%, B=32.8%, C=50%.
[0037] In a specific embodiment, the amorphous carbon satisfies: A=17.2%, B=12.8%, C=70%.
[0038] In a specific embodiment, the amorphous carbon satisfies: A=26.2%, B=19.2%, C=54.6%.
[0039] In a specific embodiment, the amorphous carbon satisfies: A=18%, B=16.9%, C=65.1%.
[0040] In a specific embodiment, the amorphous carbon satisfies: A=23.4%, B=16.2%, C=60.4%.
[0041] In a specific embodiment, the amorphous carbon satisfies: A=10%, B=24.3%, C=65.7%.
[0042] In a specific embodiment, the amorphous carbon satisfies: A=30%, B=18.4%, C=51.6%.
[0043] In a specific embodiment, the amorphous carbon satisfies: A=26.4%, B=10%, C=63.6%.
[0044] In a specific embodiment, the amorphous carbon satisfies: A=18.4%, B=30%, C=51.6%.
[0045] In a specific embodiment, the amorphous carbon satisfies: A=25.3%, B=24.7%, C=50%.
[0046] In a specific embodiment, the amorphous carbon satisfies: A=13.2%, B=16.8%, C=70%.
[0047] In the present invention, the test method of A, B and C can adopt the following steps: take an appropriate amount of amorphous carbon sample and place it in a 9mm ball sample tube, degas at 300°C for 2h, and use nitrogen as the adsorbent (P / P0 range is 0-1, where 0-0.05 is a point selected every 0.002, and 0.05-1 is a point selected every 0.05) to determine the sample adsorption amount, and obtain the pore volume of different pore size intervals by the NLDFT (Nonlocal Density Functional Theory) method, and calculate the pore volume proportions A, B, and C, and at the same time obtain the average pore size D1 of pores with a pore size of 10-100nm.
[0048] Electrochemical Devices
[0049] In the electrochemical device described in the second aspect of the present invention, it includes a negative electrode sheet, the negative electrode sheet includes a current collector and a negative electrode material layer located on the current collector, the negative electrode material layer includes the negative electrode active material and the conductive agent as described above, and the amorphous carbon and the conductive agent meet the following conditions:
[0050] 1≤D1 / D2≤10, wherein D1 is the average pore size of pores with a diameter of 10-100 nm in the amorphous carbon, and D2 is the particle size of the conductive agent.
[0051] The average pore size in the present invention refers to the average pore size formed by pores with a diameter of 10-100 nm in all amorphous carbon as a defined object.
[0052] The inventors believe that when D1 / D2 is too small, most of the conductive agent is distributed on the surface and between the particles of the amorphous carbon, and it is difficult to enter the pores with a diameter of 10-100nm in the amorphous carbon, thereby affecting the dynamics of the amorphous carbon and further affecting the cycle performance of the battery; when D1 / D2 is too large, the average pore size of the pores with a diameter of 10-100nm in the amorphous carbon is too large, and the conductive agent is easy to agglomerate inside the pores, resulting in poor dispersion effect, thereby affecting the conductive performance and causing the battery's cycle performance to decline.
[0053] In the present invention, the test method of D2 can adopt the following steps: prepare a sample of the conductive agent, place it under a transmission electron microscope for observation, arbitrarily select more than 100 particles in an area, count the diameter of each particle, and calculate the average diameter, which is the particle size of the conductive agent (the particles counted are single particles, and agglomerated particles need to be counted as monomers).
[0054] In some optional embodiments, the amorphous carbon and the conductive agent satisfy 1≤D1 / D2≤3.
[0055] In some alternative embodiments, D1 is 20-98 nm and D2 is 5-75 nm.
[0056] In some optional embodiments, the weight ratio of the amorphous carbon to the conductive agent is (10-200):1.
[0057] In some optional embodiments, the negative electrode material layer includes: the content of the negative electrode active material is 85.0wt%-99.8wt%; the content of the conductive agent is 0.1wt%-10wt%. In an optional solution, the negative electrode material layer also includes a binder, and the content of the binder is 0.1wt%-5wt%. Wherein, the content of the negative electrode material layer is the weight percentage of each component in the negative electrode material layer.
[0058] In the embodiment of the present invention, the conductive agent may be a conductive agent conventionally used in the art for preparing negative electrodes. Preferably, the conductive agent is one or more of conductive carbon black, carbon nanotubes and graphene, and more preferably conductive carbon black.
[0059] In the embodiment of the present invention, the binder may be a binder conventionally used in the art for preparing a negative electrode. For example, the following materials may be used as the binder: one or more of SBR, PAA, CMC and PVDF.
[0060] Further optionally, the negative electrode material layer also includes a thickener.
[0061] There is no particular limitation on the thickener. The addition of the thickener can increase the system viscosity of the components in the negative electrode active material layer. Generally, a sodium carboxymethyl cellulose (CMC) solution can be selected.
[0062] In a specific embodiment of the present invention, the negative electrode material layer comprises: amorphous carbon hard carbon, conductive agent carbon black, thickener sodium carboxymethyl cellulose and binder styrene-butadiene rubber.
[0063] In a specific embodiment of the present invention, the negative electrode material layer includes: 96 wt% of hard carbon, 0.5 wt% of carbon black, 1.17 wt% of sodium carboxymethyl cellulose and 2.33 wt% of styrene-butadiene rubber.
[0064] In a specific embodiment of the present invention, the negative electrode material layer includes: 80 wt% of hard carbon, 15 wt% of carbon black, 1.67 wt% of sodium carboxymethyl cellulose and 3.33 wt% of styrene-butadiene rubber.
[0065] In a specific embodiment of the present invention, the negative electrode material layer comprises: hard carbon with a content of 99.95 wt % and carbon black with a content of 0.05 wt %.
[0066] In the present invention, the current collector may be a current collector conventionally used for the negative electrode in the art, and may be a common current collector or a composite current collector. The current collector may use a material that does not cause chemical changes and has conductivity without restriction according to the actual needs of the electrochemical device. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon or aluminum-cadmium alloy, or copper, stainless steel material or aluminum-cadmium alloy surface-treated with carbon, nickel, titanium or silver may be used. In addition, in order to enhance the adhesion of the negative electrode active material, micro-embossing may be formed on the surface of the negative electrode current collector. The negative electrode current collector may be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body.
[0067] The thickness of the current collector is, for example, 16 μm.
[0068] In the present invention, the negative electrode sheet can be prepared by conventional methods in the art. For example, the following method can be used: amorphous carbon, conductive agent, thickener and binder are mixed in a certain weight ratio, and a solvent is added to mix evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the current collector; and then the negative electrode sheet is prepared through drying, rolling, cutting and other processes.
[0069] In the present invention, the electrochemical device may generally be a conventional device in the art containing the negative electrode sheet as described above, such as a secondary battery, a capacitor, and the like.
[0070] Optionally, in a specific embodiment of the present invention, the electrochemical device is a sodium ion battery, and the sodium ion battery includes the negative electrode sheet, the positive electrode sheet, the isolation membrane and the electrolyte.
[0071] In some embodiments, the positive electrode sheet is prepared by coating a positive electrode active material including a positive electrode active material on a positive electrode current collector, and a binder, a conductive agent, and a thickener may be further added as needed.
[0072] For the positive electrode current collector, it can be a current collector conventionally used for the positive electrode in the art, and can be a common current collector or a composite current collector. The positive electrode current collector can use materials that do not cause chemical changes and have high conductivity without restriction according to the actual needs of the electrochemical device. For example, stainless steel, aluminum, nickel, titanium or calcined carbon can be generally used, or aluminum or stainless steel materials surface-treated with carbon, nickel, titanium, silver, etc. In order to enhance the adhesion of the positive electrode active material, micro-embossing can be formed on the surface of the positive electrode current collector. The positive electrode current collector can be used in various forms, such as a film, a sheet, a foil, a mesh or a porous body.
[0073] In some embodiments, the isolation membrane can be a polypropylene isolation membrane or a polyethylene isolation membrane.
[0074] Wherein, the thickness of the isolation film may be 9 μm.
[0075] In a preferred embodiment, the isolation membrane is a 9 μm polyethylene membrane coated on both sides with a ceramic coating with a thickness of 2 μm.
[0076] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a sodium salt, and an additive.
[0077] Wherein, the non-aqueous solvent can be a conventional non-aqueous solvent in the art, preferably an ester solvent, and more preferably a carbonate solvent. The carbonate solvent can be selected from one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0078] Among them, the additive can be selected from one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), dithiothreitol (DTD), vinylene sulfate, 1,3-propane sultone (PS), allyl sultone and 1,4-butane sultone.
[0079] The sodium salt may be a conventional sodium salt in the art, such as NaPF6.
[0080] In the present invention, the preparation method of the sodium ion battery can be a conventional preparation method in the art, which can be a battery cell obtained by winding the positive electrode sheet, the negative electrode sheet and the isolation film, and then packaging them in a packaging shell and injecting the electrolyte; or it can be a battery cell obtained by stacking the negative electrode sheet, the isolation film, the positive electrode sheet and the isolation film in this order, and then packaging them in a packaging shell and injecting the electrolyte.
[0081] On the basis of being in accordance with the common sense in the art, the above-mentioned optional conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0082] Electronic devices
[0083] The electronic device described in the third aspect of the present invention includes the above-mentioned electrochemical device.
[0084] In the present invention, the electronic device described in the present invention can be but is not limited to mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.
[0085] Examples 1-20 and Comparative Examples 1-11
[0086] Preparation of amorphous carbon
[0087] The amorphous carbon in Examples 1-20 and Comparative Examples 1-11 is hard carbon, and the preparation method thereof adopts the following steps:
[0088] Wash coconut shells three times with a mixed solution of water and ethanol (volume ratio of 1:1), then filter, dry and grind to obtain a coconut shell precursor; put the coconut shell precursor into a crucible, heat it to 200-600°C at 1-10°C / min under a nitrogen atmosphere, and keep it warm for 2-10 hours to obtain a carbon precursor; wash the carbon precursor three times with nitric acid / hydrochloric acid / hydrofluoric acid (volume ratio of 1:1:1), then wash it with deionized water for more than 5 times, and dry it to obtain a hard carbon precursor; heat the hard carbon precursor to 1000-1500°C at 1-10°C / min under a nitrogen atmosphere, and keep it warm for 2-10 hours; then ball mill it to the desired particle size to obtain amorphous carbon, which is hard carbon.
[0089] Amorphous carbons with different pore volume distributions in Examples 1-20 and Comparative Examples 1-11 were prepared by adjusting the specific parameters of the above process. The relevant parameters of the amorphous carbons in Examples 1-20 and Comparative Examples 1-11 are listed in Table 1 below.
[0090] Among them, the test method for the pore volume and pore size of amorphous carbon is as follows: take an appropriate amount of amorphous carbon sample and place it in a 9mm ball sample tube, degas at 300°C for 2h, and use nitrogen as the adsorbent (the P / P0 range is 0-1, where 0-0.05 is a point selected for every 0.002, and 0.05-1 is a point selected for every 0.05) to determine the adsorption amount of the sample, and the pore volume in different pore size ranges is obtained by the NLDFT method, and the pore volume proportions A, B, and C are calculated, and the average pore size D1 of pores with a pore size of 10-100nm is obtained.
[0091] Testing method for conductive agent particle size: Prepare a sample of the conductive agent, place it under a scanning electron microscope for observation, select more than 100 particles in an arbitrary area, count the diameter of each particle, and calculate the average diameter, which is the particle size of the conductive agent (the particles counted are single particles, and agglomerated particles need to be counted as monomers).
[0092] The model of the conductive agent in Examples 1-20 and Comparative Examples 1-10 is TIMICAL SUPER P Li.
[0093] Preparation of negative electrode
[0094] The preparation method of the negative electrode sheet in Examples 1-20 and Comparative Examples 1-11 (the relevant parameters of the amorphous carbon and the conductive agent in Examples 1-20 and Comparative Examples 1-11 and the relationship between the amounts thereof are listed in Table 1) adopts the following steps:
[0095] According to the dosage in Table 1, amorphous carbon, conductive agent, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a weight ratio of (90-100): (1-5): 1: 2, and deionized water was added as a solvent, and stirred to mix evenly to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on a 16 μm aluminum foil current collector. After drying, rolling, cutting and other processes, the negative electrode sheets of Examples 1-20 and Comparative Examples 1-11 were prepared.
[0096] Table 1
[0097]
[0098]
[0099]
[0100] Effect Example 1
[0101] (1) Preparation of sodium ion batteries:
[0102] Preparation of positive electrode sheet: O3 type layered positive electrode material NaNi 0.34 Fe 0.33 Mn 0.33 O2, conductive carbon black (Super P), carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of (90-100):2:1:3, and a solvent N-methylpyrrolidone (NMP) is added and stirred to make the mixture uniform to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on a 16μm aluminum foil current collector. After drying, rolling, cutting and other processes, a positive electrode sheet is prepared.
[0103] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and propylene carbonate (PC) are uniformly mixed in a volume ratio of 1:1:1:1, and then dry high-purity sodium salt NaPF6 is dissolved in the above mixed solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0104] Preparation of the diaphragm: The diaphragm is a 9 μm polyethylene diaphragm coated on both sides with a ceramic coating with a thickness of 2 μm.
[0105] Preparation of sodium ion battery: The prepared positive electrode sheet, separator, negative electrode sheet of Examples 1-20 and Comparative Examples 1-11 and electrolyte are assembled in sequence, so that the positive electrode sheet, separator, negative electrode sheet of Examples 1-20 and Comparative Examples 1-11 and separator are combined alternately, and a soft-pack battery with a capacity of 1Ah is obtained through formation.
[0106] (2) The sodium ion batteries prepared according to the above method in Examples 1-20 and Comparative Examples 1-11 were tested as follows:
[0107] Test method for 2C rate retention of sodium ion battery: At a constant temperature of 25°C, charge to 4.0V at a constant current and voltage of 0.33C (constant voltage cutoff current is 0.05C), then discharge to 1.5V at a constant current of 0.33C to obtain 0.33C capacity. Charge to 4.0V at a constant current and voltage of 0.33C (constant voltage cutoff current is 0.05C), then discharge to 1.5V at a constant current of 2C to obtain 2C capacity. The ratio of 2C capacity to 0.33C capacity is recorded as 2C rate retention rate.
[0108] The test method for the energy density of sodium ion batteries is as follows: At a constant temperature of 25°C, charge to 4.0V at a constant current and voltage of 0.33C (the constant voltage cut-off current is 0.05C), and then discharge to 1.5V at a constant current of 0.33C to obtain 0.33C energy. Weigh the weight of the battery cell with a balance, and the ratio of 0.33C energy to the weight of the battery cell is the energy density.
[0109] The test method of sodium ion battery 1000cls cycle retention rate is as follows: at a constant temperature of 25℃, charge to 4.0V at a constant current and voltage of 0.5C (constant voltage cutoff current is 0.05C), and then discharge to 1.5V at a constant current of 1C. This is one cycle, and 1000 cycles are performed in this process. The ratio of the discharge capacity of the 1000th cycle to the discharge capacity of the first cycle is recorded as the 1000cls cycle retention rate.
[0110] The above test results are listed in Table 2.
[0111] Table 2
[0112]
[0113]
[0114] According to the data in Table 1, the sodium ion battery made from the amorphous carbon and the negative electrode sheet of Examples 1-20 has a 2C rate retention rate of not less than 86.9%, an energy density of not less than 131.3Wh / kg, and a 1000cls cycle retention rate of not less than 87.6%, indicating that it has excellent kinetic performance, energy density and cycle performance.
[0115] According to the results of Example 1, Example 10 and Example 11, if the weight ratio of amorphous carbon to the conductive agent is between (10-200): 1, it is more conducive to the electrical performance of the battery. For example, the weight ratios of amorphous carbon to the conductive agent in Example 10 and Example 11 are 5: 1 and 1999: 1, respectively, and the weight ratio of amorphous carbon to the conductive agent in Example 1 is 192: 1, which has better 2C rate retention, energy density and 1000cls cycle retention than those in Example 10 and Example 11.
[0116] Comparative Example 1 does not add conductive carbon black, and A, B, and C do not meet the specified conditions. The 2C rate retention rate, energy density, and 1000cls cycle retention rate are the worst.
[0117] The difference between Comparative Examples 2 and 3 and the embodiment is that D1 / D2 is not within the scope of the present invention. Combined with the data in Table 2, it can be seen that D1 / D2 that is too large or too small is not conducive to the 2C rate retention rate and the 1000cls cycle retention rate. For example, D1 / D2 of Comparative Example 2 is 0.7, and the conductive agent is mostly distributed on the surface and between the particles of the amorphous carbon. D1 / D2 of Comparative Example 3 is 10.6, and the average pore size of pores with a diameter of 10-100nm in the amorphous carbon is too large, and the conductive agent is easily agglomerated inside the pores. Compared with the embodiment, the 2C rate retention rate and 1000cls cycle retention rate of Comparative Examples 2 and 3 are significantly reduced.
[0118] The difference between Comparative Examples 4 and 5 and the embodiment is that the value of A is not within the scope of the present invention. Combining the data in Tables 1 and 2, it can be seen that A of Comparative Example 4 is 8.5%, and its energy density is reduced from at least 131.3Wh / kg in the embodiment to 119.3Wh / kg. Compared with the embodiment, the energy density of Comparative Example 4 is significantly reduced; A of Comparative Example 5 is 34.2%, and its energy density is reduced from at least 131.3Wh / kg in the embodiment to 122.7Wh / kg. Compared with the embodiment, the energy density of Comparative Example 5 is significantly reduced.
[0119] The difference between Comparative Examples 6 and 7 and the embodiments is that the value of B is not within the scope of the present invention. Combining the data in Tables 1 and 2, it can be seen that B of Comparative Example 6 is 5.6%, and its 2C rate retention rate and 1000cls cycle retention rate are only 82.1% and 78.4%; B of Comparative Example 7 is 31.8%, and its 2C rate retention rate and 1000cls cycle retention rate are only 79.5% and 83.4%. The 2C rate retention rate and 1000cls cycle retention rate of Comparative Examples 6 and 7 are significantly worse than those of the embodiments.
[0120] The difference between Comparative Examples 8 and 9 and the embodiment is that the value of C is not within the scope of the present invention. Combining the data in Tables 1 and 2, it can be seen that the C of Comparative Example 8 is 44.7%, and its 2C rate retention rate and 1000cls cycle retention rate are only 80.2% and 79.3%; the C of Comparative Example 9 is 75.2%, and its 2C rate retention rate and 1000cls cycle retention rate are only 81.7% and 81.3%. The 2C rate retention rate and 1000cls cycle retention rate of Comparative Examples 8 and 9 are significantly worse than those of the embodiment.
[0121] A, B and C of Comparative Example 10 are not within the scope of the present invention. A and B are too low, and C is too high, resulting in that compared with the embodiments, the 2C rate retention rate, energy density and 1000cls cycle retention rate of Comparative Example 10 are poor, which are 75.3%, 118.5Wh / kg and 76.4% respectively.
[0122] A, B, C and D1 / D2 of Comparative Example 11 are not within the scope of the present invention, and its A and B are too high, C is too low, and D1 / D2 is too low, resulting in that compared with the embodiments, the 2C rate retention rate, energy density and 1000cls cycle retention rate of Comparative Example 11 are poor, which are 79.5%, 124.1Wh / kg and 74.2%, respectively.
[0123] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material includes amorphous carbon, and the amorphous carbon meets the following conditions: 10%≤A≤30%, wherein A is the percentage of the total volume of pores with an inner diameter of less than 2 nm in the amorphous carbon to the total volume of pores with a diameter of less than 100 nm; 10%≤B≤30%, wherein B is the percentage of the total volume of pores with an inner diameter of 2-10 nm in the amorphous carbon to the total volume of pores with a diameter less than 100 nm; 50%≤C≤70%, wherein C is the percentage of the total volume of pores with an inner diameter of 10-100 nm in the amorphous carbon to the total volume of pores with a diameter less than 100 nm; A+B+C=100%; The amorphous carbon includes hard carbon.
2. The negative electrode active material according to claim 1, characterized in that The amorphous carbon satisfies one or more of the following conditions (a), (b) and (c): (a) 17% ≤ A ≤ 27%; (b) 16% ≤ B ≤ 24%; (c)59%≤C≤66%.
3. An electrochemical device comprising a negative electrode sheet, wherein the negative electrode sheet comprises a current collector and a negative electrode material layer located on the current collector, characterized in that: The negative electrode material layer comprises the negative electrode active material and the conductive agent as claimed in claim 1 or 2, and the amorphous carbon and the conductive agent meet the following conditions: 1≤D1 / D2≤10, wherein D1 is the average pore size of pores with a diameter of 10-100 nm in the amorphous carbon, and D2 is the particle size of the conductive agent.
4. The electrochemical device according to claim 3, characterized in that 1≤D1 / D2≤3.
5. The electrochemical device according to claim 3, characterized in that D1 is 20-98nm, and D2 is 5-75nm.
6. The electrochemical device according to claim 3, characterized in that The weight ratio of the amorphous carbon to the conductive agent is (10-200):
1.
7. The electrochemical device according to claim 3, characterized in that The negative electrode material layer includes: The content of the negative electrode active material is 85.0wt%-99.8wt%; The content of the conductive agent is 0.1wt%-10wt%; The content is the weight percentage of each component in the negative electrode material layer.
8. The electrochemical device according to claim 3, characterized in that The conductive agent is carbon black.
9. The electrochemical device according to any one of claims 3 to 8, characterized in that: The electrochemical device is a sodium ion battery.
10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in any one of claims 3 to 9.
Citation Information
Patent Citations
Lithium ion battery cathode material and preparation method thereof and lithium ion battery
CN110635117A
Negative electrode material as well as negative electrode plate and battery comprising negative electrode material
CN115863574A
Negative active material and preparation method thereof, negative pole piece and secondary battery
CN116885173A
Electrochemical apparatus and electronic apparatus
US20240250260A1
Negative electrode, electrochemical apparatus and electronic apparatus
WO2022266797A1